On the examination of out-of-pocket health expenditures in India, Pakistan, Sri Lanka, Maldives, Bhutan, Bangladesh and Nepal - Shaikh, Imlak Shaikh; Singh, Shabda (Business: Theory and Practice, 2017)
The aim of this study is to analyze the healthcare expenditures in seven South Asian countries namely, India, Pakistan, Sri Lanka, Maldives, Bhutan, Bangladesh and Nepal. The longitudinal data has been taken for 19 years from 1995 to 2013. We specifically examine the out-of-pocket healthcare expenditure in these countries. The per-capita health expenditure differences have been compared. We also develop panel data pooled OLS model for out-of-pocket expenditure with the factors affecting it, i.e. per capita health expenditure, household final consumption expenditure and public health expenditure. The work is in line with the earlier studies of determinants of out-of-pocket health expenditures. The results suggest that Maldives has the highest per capita health expenditure while out-of-pocket health expenditure as a percentage of total expenditure on health is highest for the India. The fixed and random effect is evidenced on health expenses across the years and cross section based on various determinants. The novel aspect of the work is that, this is an attempt to explain healthcare financing in the developing economies. The key determinant of out-of-pocket expenditure is the final household expenditures as the percentage of gross domestic product.